Synthesis and Evaluation of Antibacterial and Antitumor Activities of Apigenin Derivatives - Feng, Ling; Cao, Ya-Kun; Li, Yang; Song, Zhi-Fang; Huai, Qi-Yong (Asian Journal of Chemistry, 2015)
Using nicotinic acid, isonicotinic acid reacted with apigenin via DCC condensation to produce apigenin derivatives. Their chemical structure was confirmed by MS and 1H NMR spectroscopy. The antimicrobial activities of the new compounds and raw materials were explored with Staphylococcus aureus and Acinetobacter. while the antitumor activities of the new compounds and raw materials were explored with SH-SY5Y, MCF-7, HepG2 under the same conditions. The results show that apigenin derivatives have stronger antibacterial properties on Acinetobacter than Staphylococcus. The new compounds have the strongest antitumor activities on HepG2, followed by MCF-7 and relative weak activities on SH-SY5Y in vitro.